Validitas Media Pembelajaran Komik Dea pada Materi Perubahan Wujud Benda Bagi Peserta Didik Disabilitas Intelektual di Sekolah Luar Biasa - Widea Febrianti; Setia Budi; Zulmiyetri Zulmiyetri; Safaruddin Safaruddin (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the validity of the DEA (Digital Educational Adaptive) comic media developed on the material of changes in the form of objects for students with mild intellectual disabilities. The study used the Research and Development (R&D) method with the ADDIE model, but its implementation was limited to the product validation stage. The validation process was carried out by two groups of validators, namely material experts and media experts. Data were collected through a questionnaire using a Likert scale, then analyzed using a quantitative descriptive approach and supported by qualitative analysis of the validators' suggestions. The results showed that the DEA (Digital Educational Adaptive) comic media had a very high level of validity. The assessment from material experts obtained a percentage of 95%, while the assessment from media experts reached 86%. The average overall percentage of 90.5% was in the very valid category. These results indicate that the DEA comic media is suitable for use as a learning medium on the material of changes in the form of objects for students with mild intellectual disabilities based on the results of expert validation. This study has implications for the availability of digital learning media that have met the validity aspects, so that it can be an alternative in supporting more adaptive learning. Further research is recommended to continue to the practicality and effectiveness testing stages through media implementation in the learning process.